2002
DOI: 10.1200/jco.2002.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Chemotherapy or Watchful Waiting? A Vignettes Study Among Oncologists

Abstract: Patients will encounter different decisions depending on their oncologists' preferences and their own personal background. Therefore, to ensure adequate information for decision-making processes, decision aids are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 42 publications
2
24
0
2
Order By: Relevance
“…Best supportive care is often perceived as 'doing nothing' (Charles et al, 1998). For medical oncologists, the patient's wish is an important determinant of their own preference for treatment (Charles et al, 1998;Koedoot et al, 2002). Moreover, they also prefer to 'do something', that is, offering chemotherapy, rather than offering best supportive care (de Haes and Koedoot, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Best supportive care is often perceived as 'doing nothing' (Charles et al, 1998). For medical oncologists, the patient's wish is an important determinant of their own preference for treatment (Charles et al, 1998;Koedoot et al, 2002). Moreover, they also prefer to 'do something', that is, offering chemotherapy, rather than offering best supportive care (de Haes and Koedoot, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those of a study in the United States, which found that 22% of patients with NSCLC who had already received chemotherapy would choose chemotherapy over best supportive care for a survival benefit of 3 months (10). However, in clinical practice only a small proportion of patients with cancer actually refuse chemotherapy (12). One possible reason for patients' willingness to undergo chemotherapy is that they have overly optimistic expectations of the results of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thematic file 16 vignettes cliniques de patients en différentes situations palliatives sont présentées à 697 oncologues devant se déterminer sur le choix d'un traitement spécifi que ou non [33]. L'âge du patient, son désir de poursuivre la chimiothérapie et l'espérance de survie sont les principaux paramètres déterminant le choix thérapeutique.…”
Section: Dossierunclassified